2016
DOI: 10.7448/ias.19.1.20944
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of hepatitis C virus infection and HIV viral load: new insights into epidemiologic synergy

Abstract: IntroductionHepatitis C virus (HCV) and HIV infection frequently co-occur due to shared transmission routes. Co-infection is associated with higher HCV viral load (VL), but less is known about the effect of HCV infection on HIV VL and risk of onward transmission.MethodsWe undertook a systematic review comparing 1) HIV VL among ART-naïve, HCV co-infected individuals versus HIV mono-infected individuals and 2) HIV VL among treated versus untreated HCV co-infected individuals. We performed a random-effects meta-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
1
4
1
Order By: Relevance
“…At the end of tuberculosis treatment, 76% of hepatitis B infected HAART patients had less than II clinical stages, but 90% of hepatitis B free HAART patient had less than II clinical stages. The finding was in line with the 2016 systematic review report [ 45 ]. This is because of the effects of hepatitis B and hepatitis C viral infection on the immune system of the host that leads them to the poor response to treatments [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…At the end of tuberculosis treatment, 76% of hepatitis B infected HAART patients had less than II clinical stages, but 90% of hepatitis B free HAART patient had less than II clinical stages. The finding was in line with the 2016 systematic review report [ 45 ]. This is because of the effects of hepatitis B and hepatitis C viral infection on the immune system of the host that leads them to the poor response to treatments [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our results on the effect of HCV on VL in ART-naïve individuals are not in agreement with a meta-analysis reporting no difference in VL by HCV co-infection status [5]. However, the primary outcome in this meta-analysis was based on the mean VL difference from a single VL measurement and most of the included studies did not account for HIV and HCV infection duration [5]. Interestingly, 4 of the 15 individual studies in the meta-analysis reported a significantly higher VL among HIV mono-infected individuals, which was also observed in our main analysis during the first year following HCVsc.…”
Section: Discussioncontrasting
confidence: 84%
“…HIV infection often precedes HCV infection in MSM. This differs from the main risk groups in early studies of HIV/HCV co-infection, people who inject drugs (PWID) and haemophiliacs, in whom HCV was generally acquired before HIV infection [4,5].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations